Răspuns:
a)
[tex]=\sqrt{2} +\sqrt{6} (\frac{\sqrt{3}+\sqrt{2}}{\sqrt{6}})-6\sqrt{6}((\frac{\sqrt{2}-\sqrt{3}}{\sqrt{9*6}})-3\sqrt{3} =[/tex]
[tex]=\sqrt{2} +\sqrt{3}+\sqrt{2}-6\sqrt{6}(\frac{\sqrt{2}-\sqrt{3}}{3\sqrt{6}})-3\sqrt{3} =[/tex]
[tex]=2\sqrt{2} +\sqrt{3}-2(\sqrt{2}-\sqrt{3})-3\sqrt{3} =[/tex]
[tex]=2\sqrt{2} +\sqrt{3}-2\sqrt{2}+2\sqrt{3}-3\sqrt{3} =[/tex]
[tex]=0[/tex]
b)
[tex]=\sqrt{6*4} (\frac{7\sqrt{3}-5\sqrt{2}}{\sqrt{6}} )-3\sqrt{6} (\frac{6\sqrt{3}-5\sqrt{2}}{\sqrt{6}} )-\sqrt{25*2} =[/tex]
[tex]=2(7\sqrt{3}-5\sqrt{2})-3(6\sqrt{3}-5\sqrt{2}})-5\sqrt{2} =[/tex]
[tex]=14\sqrt{3}-10\sqrt{2}-18\sqrt{3}+15\sqrt{2}}-5\sqrt{2} =[/tex]
[tex]=-4\sqrt{3}[/tex]
Explicație pas cu pas: